TRANSFORMATIONAL LEADERSHIP AS A CATALYST FOR TEACHER PERFORMANCE AND EDUCATIONAL INNOVATION IN THE DIGITAL AGE - Zahwa Rifqotul Maula; Salsabila Nur Hamidah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyse the transformative leadership of the headteacher in enhancing teacher performance and educational innovation in the digital age at MTs Hidayatus Sholihin Turus-Gurah-Kediri. The study employs a qualitative approach using a case study design. Data were collected through in-depth interviews, observations and documentation involving the headteacher, deputy headteacher, teachers, school administrators and pupils. Data analysis was conducted using the interactive model developed by Miles, Huberman and Saldana, comprising the stages of data collection, data condensation, data presentation, and the drawing and verification of conclusions. The research findings indicate that the headteachers have implemented transformative leadership through the development of a shared vision, the provision of motivation, intellectual stimulation, professional development for teachers, and guidance on the use of digital technology. These strategies have led to improvements in teachers’ digital competence, discipline, innovation , collaboration and performance. The implementation of transformative leadership is supported by the commitment of madrasah heads, a collaborative work culture, and the availability of technological resources; however, it still faces challenges in the form of disparities in teachers’ digital competence, infrastructure limitations, and resistance to change. The implications of this research suggest that transformative leadership is an effective approach in supporting digital transformation and improving the quality of education in madrasahs